Draft Annual Plan 1978-79 Himachal Pradesh - Planning Commission (Planning Commission, 1978)
The Fifth Plan (1974-75 to 1978-79) was launched in a very optimistic atmosphere on 1st April, 1974. At 1972-73 price levels the size of the Fifth Plan was put around double the size of the Fourth Plan. The total fourth Plan expenditure was Rs. 113.43 crores and the draft Fifth Plan size was envisaged at Rs. 231.40 crores. Later on, when the National Development Council met in September, 1976 to finalize the Fifth Plan, the size of Himachal’s Fifth Plan was fixed at Rs. 238.95 crores. In fact the Fifth Plan did not have a good start in the face of highest ever price hike and mounting inflationary pressures as a result of which the flow of funds during first two years of the Fifth Plan was much less as compared to the proportionate norms. the total plan outlays for 1974-75 and 1975-76 were Rs. 30.66 crores and Rs. 32.58 crores against which an expenditure of Rs. 30.80 crores and Rs. 33.02 crores, respectively, was recorded.
Planning Department, Himachal Pradesh